2019
DOI: 10.1021/acs.langmuir.9b02960
|View full text |Cite
|
Sign up to set email alerts
|

Do Columns of Azobenzene Stars Disassemble under Light Illumination?

Abstract: The clustering properties of star-shaped molecules comprising three photochromic azobenzene-containing arms are investigated with specific focus on the influence of light on these structures. Previous experimental works report self-assembly of azobenzene stars in aqueous solution into long columnar clusters that are detectable using optical microscopy. These clusters appear to vanish under UV irradiation, which is known to induce trans-to-cis photoisomerization of the azobenzene groups. We have performed MD si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 75 publications
(144 reference statements)
3
32
0
2
Order By: Relevance
“…In this work we investigate aqueous solutions of azobenzene star molecules with a planar benzene-1,3,5-tricarboxamide (BTA) core and three azo arms (azo-BTA star) ( Figure 1a). This star can be classified as rigid and quasi planar in its all-trans state, as we have found recently [14,29]. Its BTA core is a well-known supramolecular entity in colloid science, used for the fabrication of dynamic and responsive materials [40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…In this work we investigate aqueous solutions of azobenzene star molecules with a planar benzene-1,3,5-tricarboxamide (BTA) core and three azo arms (azo-BTA star) ( Figure 1a). This star can be classified as rigid and quasi planar in its all-trans state, as we have found recently [14,29]. Its BTA core is a well-known supramolecular entity in colloid science, used for the fabrication of dynamic and responsive materials [40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 85%
“…The quantification of the interactions is our next task. Partially, this task has been solved recently by us [29] for the same object of the study. In that article we have shown that the binding along the column is much stronger (up to a factor of six) as compared to the intercolumnar coupling.…”
Section: Analysis Of the Trans-azo-bta Star Crystalmentioning
confidence: 99%
See 3 more Smart Citations